2016
DOI: 10.1007/s12035-016-9855-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation

Abstract: Fragile X mental retardation protein (FMRP), associated with fragile X syndrome, is known as an RNA-binding protein to regulate gene expression at post-transcriptional level in the brain. FMRP is also involved in microRNA (miRNA) biogenesis during the process of precursor miRNA (pre-miRNA) into mature miRNA. However, there is no description of the effect of FMRP on primary miRNA (pri-miRNA) processing. Here, we uncover a novel role of FMRP in pri-miRNA processing via controlling Drosha translation. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 65 publications
(87 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, we found that the FMRP-phosphomimic S500D binds to miR-125a (Fig 5B), whereas the unphosphoryated protein does not (Fig 5A), even at high protein: RNA concentrations (S4 Fig). This is a novel finding, as previously it has been shown that phosphorylated FMRP associates with precursor microRNAs [56, 57], and that FMRP can anneal mature miRNAs onto their mRNA targets [37], but not that depending on its phosphorylation status FMRP could function as a switch in binding mature miRNAs. The binding of miR-125a is specific, as an unrelated miRNA, miR-122, is not bound by FMRP S500D (Fig 5E).…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, we found that the FMRP-phosphomimic S500D binds to miR-125a (Fig 5B), whereas the unphosphoryated protein does not (Fig 5A), even at high protein: RNA concentrations (S4 Fig). This is a novel finding, as previously it has been shown that phosphorylated FMRP associates with precursor microRNAs [56, 57], and that FMRP can anneal mature miRNAs onto their mRNA targets [37], but not that depending on its phosphorylation status FMRP could function as a switch in binding mature miRNAs. The binding of miR-125a is specific, as an unrelated miRNA, miR-122, is not bound by FMRP S500D (Fig 5E).…”
Section: Discussionmentioning
confidence: 58%
“…Recently, in a FXS mice model, FMRP was shown to participate in pri-miRNA processing by upregulating DROSHA expression at the translational level. Loss of FMRP was associated with accumulation of specific pri-miRNAs and reduction of pre-miRNAs (Wan et al, 2017).…”
Section: Non-coding Rna Mediated Mechanisms In Fxs Pathophysiologymentioning
confidence: 99%
“…4b). Moreover, When an exogenous vector pFRT-TODestFLAGHAhFMRPiso13334, purchased from Addgene (Addgene Plasmid #48690) with Drosha expression enhancing ability, was co-transfected with msgRNA-ALA plasmid, the relative LIG4 expression declined to about 50% (Fig. 4b),…”
Section: Resultsmentioning
confidence: 99%